Serum catestatin concentrations are decreased in obese children and adolescents. Issue 5 (21st April 2019) - Simunovic, Marko; Supe‐Domic, Daniela; Karin, Zeljka; Degoricija, Marina; Paradzik, Martina; Bozic, Josko; Unic, Ivana; Skrabic, Veselin
Abstract : Background: Catestatin is a chromogranin A‐derived peptide with a wide spectrum of biological activities, such as inhibiting catecholamine release, decreasing blood pressure, stimulating histamine release, reducing beta‐adrenergic stimulation, and regulating oxidative stress. Objectives: The aims of our study were to determine serum catestatin concentrations in obese children and adolescents in regard to presence or absence of metabolic syndrome (MS) and to evaluate the possible relations between catestatin levels and other cardiovascular risk factors. Subjects: Ninety‐two obese subjects with a body mass index z score > 2, aged 10 to 18 years, and 39 healthy, normal weight controls were enrolled in the study. Methods: Serum catestatin concentrations were measured using an enzyme‐linked immunosorbent assay. Results: Significantly lower serum catestatin concentrations were recorded in the group of obese subjects compared with a control group (10.03 ± 5.05 vs 13.13 ± 6.25 ng/mL, P = 0.004). Further analyses revealed significantly lower catestatin concentrations in the subgroup of obese patients with MS (9.02 ± 4.3 vs 10.54 ± 5.36 vs 13.13 ± 6.25, P = 0.008). Serum catestatin concentrations were significantly negatively correlated with diastolic blood pressure ( r = −0.253, P = 0.014), homeostatic model assessment of insulin resistance ( r = −0.215, P = 0.037) and high sensitivity C‐reactive protein ( r = −0.208, P = 0.044). Conclusions: To the best of our knowledge, this study is the first to report catestatin concentrations in obese children and adolescents and their possible relations with MS and cardiovascular risk factors in a pediatric population. Obese subjects with MS have lower serum catestatin concentrations than obese subjects without MS and controls.